ISOLASI DAN IDENTIFIKASI GOLONGAN SENYAWA TOKSIK DARI DAGING BUAH PARE (Momordica charantia L.) - I G. A. Gede Bawa (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2009)
Isolation and identification of toxic compounds were conducted to snake fruit (Momordica charantia L.).Maseration of 600 grams dried fruit in methanol resulted in 54.250 grams dark green extract which were toxic tobrine shrimp (Artemia salina Leach) with an LC50 = 74.99 ppm. When the extract was dissolved in water andpartitioned using n-hexane and chloroform three extracts were obtained. The n-hexane extract was found to be themost toxic to brine shrimp (LC50 = 130.439 ppm).Separation of the n-hexane extract using column chromatography resulted in 7 fractions. The most toxicfraction (F), LC50 = 33.83 ppm, was pure based on TLC.FTIR analyses showed that the active components of the extract contains triterpenoides characterized by CHaliphatic groups (CH2, CH3), binded O-H, C-O, C=C, and C=O. UV-Vis spectra showed absorption at 274,2 and432,8 nm suggesting an n * electronic transition.